2011
DOI: 10.1093/brain/awr122
|View full text |Cite
|
Sign up to set email alerts
|

Shaping reversibility? Long-term deep brain stimulation in dystonia: the relationship between effects on electrophysiology and clinical symptoms

Abstract: Long-term results show that benefits from chronic deep brain stimulation in dystonia are maintained for many years. Despite this, the neurophysiological long-term consequences of treatment and their relationship to clinical effects are not well understood. Previous studies have shown that transcranial magnetic stimulation measures of abnormal long-term potentiation-like plasticity (paired associative stimulation) and GABAa-ergic inhibition (short-interval intracortical inhibition), which are seen in dystonia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 31 publications
6
113
2
Order By: Relevance
“…LTP-like plasticity in the motor cortex is impaired in PD, particularly in patients with dyskinesias 37. In patients with dystonia treated with globus pallidus pars interna DBS, it has been suggested that changes in LTP-like plasticity in the motor cortex may drive the improvement in dystonia 38 39. Whether restoration of sensorimotor integration by long-term STN DBS is related to LTP-like plasticity mechanisms requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…LTP-like plasticity in the motor cortex is impaired in PD, particularly in patients with dyskinesias 37. In patients with dystonia treated with globus pallidus pars interna DBS, it has been suggested that changes in LTP-like plasticity in the motor cortex may drive the improvement in dystonia 38 39. Whether restoration of sensorimotor integration by long-term STN DBS is related to LTP-like plasticity mechanisms requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…The response to DBS for dystonia is more similar to that of depression, as it develops gradually and maximum effect is seen only after months of stimulation (Yianni et al, 2003). In dystonia and depression, neuroplasticity and CNS remodeling may be critical to the long-term treatment response to DBS (Ruge et al, 2011; Gibson et al, 2014). Indeed, changes in serum levels of brain-derived neurotrophic factor are abnormally low and increase with antidepressant treatment (Brunoni et al, 2008, meta-analysis) and in response to chronic DBS in an animal model (Hamani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interindividual differences (endophenotype), such as the levels of cortical plasticity, may play a role in the beneficial effect of DBS 73 74…”
Section: Literature Analysis According To the Expected Outcomementioning
confidence: 99%